2017
DOI: 10.7326/m17-0188
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Whole-Genome Sequencing on the Primary Care and Outcomes of Healthy Adult Patients

Abstract: Background Whole-genome sequencing (WGS) in asymptomatic adults might prevent disease but increase healthcare utilization without clinical value. Objective Describe the effect on clinical care and outcomes of adding WGS to standardized family history assessment in primary care. Design Pilot randomized trial. Setting Academic primary care practices. Participants Nine primary care physicians (PCPs) and 100 generally healthy patients aged 40–65. Interventions Patients were randomly assigned to receive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
161
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(168 citation statements)
references
References 39 publications
3
161
0
4
Order By: Relevance
“…Coupled with growing knowledge of how such genomic variation relates to health, disease and treatment options, these findings suggest that whole genome sequencing can benefit routine health care in Canada's future. Despite a considerable burden of uncertainty, and the possibility that falsepositive findings may engender follow-up investigations 51 and a "worried well" population, 70 incorporation of sequence-based family history should serve to enhance personalized patient care. somal), Neal Sondheimer (mitochondrial) and Iris Cohn (pharmacogenomics) interpreted the genomic variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coupled with growing knowledge of how such genomic variation relates to health, disease and treatment options, these findings suggest that whole genome sequencing can benefit routine health care in Canada's future. Despite a considerable burden of uncertainty, and the possibility that falsepositive findings may engender follow-up investigations 51 and a "worried well" population, 70 incorporation of sequence-based family history should serve to enhance personalized patient care. somal), Neal Sondheimer (mitochondrial) and Iris Cohn (pharmacogenomics) interpreted the genomic variants.…”
Section: Resultsmentioning
confidence: 99%
“…40 This variant was recently interpreted as likely pathogenic in another healthy cohort. 51 However, it is as frequent as 0.1% in some populations (http://gnomad.broadinstitute.org/), which suggests that the variant is either unrelated to disease or functions with incomplete penetrance. Additional variants, as observed in CDH1, CHMP2B and KCNE2, have been published as disease alleles, with functional support, albeit with discordance in the literature and databases.…”
Section: Personal Genome Sequencing and Medical Annotationmentioning
confidence: 99%
“…In addition, it is increasingly clear that what happens downstream of genetic testing is also a critical determinant of payers' skepticism (Kohane, Hsing, and Kong 2012;Vassy et al 2017). For example, a 2005 randomized controlled trial of genetic testing for Alzheimer's disease found that individuals who tested positive were 5.76 times more likely to adjust their long-term insurance plans (Zick et al 2005).…”
Section: Pharmacogenomic Testing Strategiesmentioning
confidence: 99%
“…Опубликованные в 2017 г. результаты дру-гого исследования ставит под сомнение це-лесообразность использования технологии полного секвенирования генома в рамках оказания первичной медицинской помощи [26]. С участием 100 здоровых пациентов 40-65 лет и их лечащих врачей было сделано полногеномное секвенирование для половины участников экспертимента.…”
Section: анализ направлений и рисков развития технологий персонализирunclassified
“…При этом, несмотря на выявленные мутации, видимых нарушений состояния здоровья испытуемых обнаружено не было. Хотя ученые по-прежнему оптими-стично настроены в отношении применения технологии CRISPR-Cas9, они рекомендуют своим коллегам более внимательно изучать внецелевые эффекты любого редактирования генов.Опубликованные в 2017 г. результаты дру-гого исследования ставит под сомнение це-лесообразность использования технологии полного секвенирования генома в рамках оказания первичной медицинской помощи [26]. С участием 100 здоровых пациентов 40-65 лет и их лечащих врачей было сделано полногеномное секвенирование для половины участников экспертимента.…”
unclassified